THE UTILIZATION OF THE DHIKR METHOD AS A STRATEGY FOR MENTAL HEALTH REHABILITATION AMONG INDIVIDUALS WITH SUBSTANCE ADDICTION AT PONDOK TETIRAH DHIKR REHABILITATION CENTER, YOGYAKARTA - Ganjar Ahmad Ripai; Novia Fetri Aliza (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2024)
This study investigates the application of the dhikr method as an intervention to restore mental health among individuals recovering from substance addiction at the Pondok Tetirah Dhikr Rehabilitation Center in Yogyakarta. Employing a qualitative research design, the study engaged four participants, utilizing data collection techniques that included observation, interviews, and document analysis. The data were analyzed using the Miles and Huberman framework, which comprises data reduction, data display, and conclusion drawing. Data credibility was ensured through triangulation techniques. The findings reveal that addressing mental health challenges in individuals with substance addiction involves the structured application of dhikr practices. Two specific forms of dhikr are implemented: dhikr jahri, which involves vocal recitation of the phrase la ilaha illallah, and dhikr khafi, characterized by silent remembrance of Allah in the heart. Participants reported significant positive changes, including increased emotional tranquility, cessation of drug use, and the absence of self-harming or aggressive behaviors. The transformative effects of these practices highlight the role of spiritual engagement in mitigating mental health disorders. Moreover, the peace experienced by the participants signifies a reduction in the psychological distress they faced upon admission to the rehabilitation center. The study underscores the importance of integrating spiritual practices, such as dhikr, within the broader framework of mental health interventions for individuals recovering from substance addiction.